2013
DOI: 10.1016/j.ajog.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effects of metformin on obesity-associated endometrial proliferation

Abstract: Objective Obesity is a significant contributing factor to endometrial cancer risk. We previously demonstrated that estrogen-induced endometrial proliferation is enhanced in the context of hyperinsulinemia and insulin resistance. In this study we investigate whether pharmacologic agents that modulate insulin sensitivity or normalize insulin levels will diminish the proliferative response to estrogen. Study Design Zucker fa/fa obese rats and lean controls were used as models of hyperinsulinemia and insulin res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 20 publications
(26 reference statements)
1
33
0
1
Order By: Relevance
“…Metformin resulted in G1 phase cell cycle arrest, induction of apoptosis and decreased human telomerase reverse transcriptase expression in endometrial cancer cells (50,55). Treatment with metformin attenuates the estrogen-dependent proliferative expression of c-myc and c-fos in the obese rat endometrium, an effect which was accompanied by inhibition of the phosphorylation of insulin and IGF1 receptors, as well as Erk 1/2 (17,55). In vitro studies have indicated that metformin inhibits rat endometrial cell line proliferation and suppresses endometrial cancer cell growth via cell cycle arrest and concomitant autophagy and apoptosis (55,56).…”
Section: Metformin and Endometrial Cancermentioning
confidence: 97%
See 3 more Smart Citations
“…Metformin resulted in G1 phase cell cycle arrest, induction of apoptosis and decreased human telomerase reverse transcriptase expression in endometrial cancer cells (50,55). Treatment with metformin attenuates the estrogen-dependent proliferative expression of c-myc and c-fos in the obese rat endometrium, an effect which was accompanied by inhibition of the phosphorylation of insulin and IGF1 receptors, as well as Erk 1/2 (17,55). In vitro studies have indicated that metformin inhibits rat endometrial cell line proliferation and suppresses endometrial cancer cell growth via cell cycle arrest and concomitant autophagy and apoptosis (55,56).…”
Section: Metformin and Endometrial Cancermentioning
confidence: 97%
“…Although various anticancer effects of metformin have previously been described (1,2,(15)(16)(17)(18)(19)(20)24,25), the suppression of LKB1-mediated mTOR signaling is hypothesized to be the fundamental mechanism underlying these effects. Metformin has been demonstrated to be associated with reduced risk and enhanced overall survival rates of several obesity-associated types of cancer, although variable results have been obtained between studies.…”
Section: Metformin Mechanism Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…While circulating insulin levels reflect systemic responses to metformin, and are easily measured, additional tissue-specific biomarkers of metformin are necessary to assess metformin response in the endometrium. General markers of proliferation, such as Ki67 and PCNA, have some utility but may not be sufficiently sensitive to reflect tissue response to short-term metformin use [17].…”
Section: Discussionmentioning
confidence: 99%